An analysis of health-related quality of life in the phase III PROSELICA and FIRSTANA studies assessing cabazitaxel in patients with metastatic castration-resistant prostate cancer - Thiery-Vuillemin, A. (ESMO Open, 2021)
BACKGROUND: Men with metastatic castration-resistant prostate cancer (mCRPC) are living longer, therefore optimizing health-related quality of life (HRQL), as well as survival outcomes, is important for optimal patient care. The aim of this study was to assess the HRQL in patients with mCRPC receiving docetaxel or cabazitaxel. PATIENTS AND METHODS: PROSELICA (NCT01308580) assessed the non-inferiority of cabazitaxel 20 mg/m(2) (C20) versus 25 mg/m(2) (C25) in patients with mCRPC after docetaxel. FIRSTANA (NCT01308567) assessed the superiority of C25 or C20 versus docetaxel 75 mg/m(2) (D75) in patients with chemotherapy-naive mCRPC. HRQL and pain were analyzed using protocol-defined, prospectively collected, Functional Assessment of Cancer Therapy—Prostate (FACT-P) and McGill-Melzack questionnaires. Analyses included definitive improvements in HRQL, maintained or improved HRQL, and HRQL over time. RESULTS: In total, 2131 patients were evaluable for HRQL across the two studies. In PROSELICA, 38.8% and 40.5% of patients receiving C20 and C25, respectively, had definitive FACT-P total score (TS) improvements. In FIRSTANA, 43.4%, 49.7%, and 44.9% of patients receiving D75, C20, and C25, respectively, had definitive FACT-P TS improvements. In both trials, definitive improvements started after cycle 1 and were maintained for the majority of subsequent treatment cycles. More than two-thirds of patients maintained or improved their FACT-P TS. CONCLUSIONS: In PROSELICA and FIRSTANA, >40% of the 2131 evaluable patients with mCRPC had definitive FACT-P TS improvements; improvements occurred early and were maintained. More than 75% of patients maintained or improved their FACT-P TS.